Pengaruh Sikap Anti-Intellectualism dan Faktor Demografis Terhadap Persepsi Mahasiswa Mengenai Etika - Nanik Lestari; Nurul Aisyah Rachmawati; Oktaviani Oktiviani (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2014)
The researches aimed are first, examine the influence psychological variables is anti-intellectualism attitude towards perceptions of students regarding ethics, especially ethics related information technology (IT). Secondly, examine the influence demographic factors on perception of students regarding especially ethics related information technology (IT). Demographic variables are proxy: age (AGE), sex (gender), works status and marital status (OCCUPMARRIT). Method of collecting data by using a questionnaire that was distributed on the mailing list active student graduate school of Accounting Sciences Faculty of Economics University of Indonesia, and a total number of 33 final questionnaires. The results of this study are: firstly, we found evidence that the more a person‟s anti-intellectualism, then the higher the tendency to commit fraud (notethical), and thus the attitude of influential anti-intellectualism against negative perceptions of students regarding the ethics of IT. Secondly, we found evidence that the demographic variables of sex (GENDER) significantly affect students‟ perceptions regarding the ethics of TI, or the other words female students tend not to do the cheating when compared with male students. Finally, those other demographic variables are age (AGE) and works status and marital status (OCCUPMARRIT) does not affect students‟ perceptions regardingthe ethics IT.